Arterial adaptations to training among first time marathoners. Issue 1 (December 2015) - Hafner, Nicole; Womack, Christopher; Luden, Nicholas; Todd, Mikel
Abstract Background Exercise training favorably alters arterial anatomy in trained limbs, though the simultaneous effects on passively trained arteries are unclear. Thus, brachial (non-trained limb), popliteal (trained limb) and carotid total wall thickness (TWT), wall-to-lumen ratios (W:L), intima-media thickness (IMT) and lumen diameters (LD) were compared between experimental (n = 14) and control (n = 11) participants before and after the experimental participants participated in marathon training. Methods Arterial dimensions were measured with B-mode ultrasonography. Initial and final testing of VO2max and running speed at 3.5 mmol lactate were measured in the experimental group. Results VO2max was unchanged by training, but running speed at 3.5 mmol lactate increased by 5 % (p = .008). Time by group interactions were observed for the brachial and popliteal measures (p < 0.05), but not the carotid. No changes were observed in the control group. Prior to the intervention the experimental group had larger LD in the brachial (p = .002) and popliteal arteries (p = .007) than controls; no other pre-testing differences were found. Following training, TWT declined in the brachial (pre = .99 ± .16 mm; post = .84 ± .10 mm;p = .007) and popliteal (pre = .96 ± .09 mm; post = .86 ± .11 mm;p = .005) arteries, characterized by a 0.07 mm decrease in brachial IMT (p = .032) and a non-significant 0.03 mm reduction in popliteal IMT. LD increased in the brachial (pre = 3.38 ± .35 mm; post = 3.57 ± .41 mm;p = .015) and popliteal (pre = 4.73 ± .48 mm; post = 5.11 ± .72 mm;p = .002) arteries. Conclusions These data suggest that exercise-induced alterations in arterial dimensions occur in trained and non-trained limbs, and that adaptations may be dose dependent.